Validation of resilient and drought adapted forage options in Senegal - Report 2023-2024 - Faye, Aliou; Ndiaye, Junior Bruno; Ka, Seynabou Harandé; Van Der Hoek, Rein; Jauregui, Rosa Noemi (2024)
This report presents the partial and preliminary results of the forage trials in Senegal implemented in 2023 and 2024 by ISRA-CERAAS as part of the CGIAR Research Initiative on Accelerated Breeding (ABI). Multi-locational agronomic evaluation of the performance of resilient and drought adapted cultivars and hybrids of Urochloa (Brachiaria) and Megathyrsus (Panicum) grasses identified promising options for two different regions in the country. In general the Brachiaria hybrids showed better drought resilience and stronger regrowth after the dry season than the other materials. The performance of these forages indicates that they can constitute an important additional feed source for ruminants in the Sahelo-Sudanian zone, which face chronic forage deficits affecting their productivity.